SEBARAN BANGUNAN PILLBOX SEBAGAI STRATEGI PERTAHANAN JEPANG DI TELUK AMBON - Muhammad Al Mujabuddawat; Wuri Handoko (Forum Arkeologi, 2018)
One characteristic of the Japanese defense system is the existence of pillboxes. During the Japanese occupation of Ambon Island, the construction of the pillboxes was carried out in massive numbers as a defense strategy to anticipate attacks by the Allies who wanted to retake Ambon Island territory. The purpose of this study was to determine the distribution pattern of Pillboxes and analyze the distribution of Pillboxes as part of the Japanese defense strategy in defending Ambon Bay. The data collection method uses the field observation method along the coast of the Ambon Bay which is the entrance of the sea traffic and airlines. This location is the center of settlements and government so that almost all strategic infrastructure is in this region — spatial data obtained from each pillbox object coupled with the Architectural Documentation Center (PDA) inventory data in 2007, then associated with related literature data, processed using Geographic Information System applications to produce the descriptive analysis. The results of this study indicate that the distribution of pillboxes location is generally divider into coastal and hilly locations and there are concentrations in strategic areas. The general conclusion of this study is the pillboxes placement strategy is an effective strategy both in attack and defense.